2015
DOI: 10.1175/jcli-d-15-0185.1
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Projections of Regional Climatic Changes over Ontario, Canada

Abstract: In this study, high-resolution climate projections over Ontario, Canada, are developed through an ensemble modeling approach to provide reliable and ready-to-use climate scenarios for assessing plausible effects of future climatic changes at local scales. The Providing Regional Climates for Impacts Studies (PRECIS) regional modeling system is adopted to conduct ensemble simulations in a continuous run from 1950 to 2099, driven by the boundary conditions from a HadCM3-based perturbed physics ensemble. Simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…On a local scale, for sub-hourly and up to 6-hourly extreme precipitation, increases at or above the C-C rate have been found in the Netherlands (Lenderink and van Meijgaard, 2008;Lenderink et al, 2017), Switzerland (Ban et al, 2014), Germany (Berg et al, 2013), the UK (Blenkinsop et al, 2015), the Mediterranean (Drobinski et al, 2016), most of Australia Sharma, 2015, 2017;Schroeer and Kirchengast, 2017), North America (Shaw et al, 2011), and China (Miao et al, 2016), while in India (Ali and Mishra, 2017) and northern Australia (Hardwick Jones et al, 2010) negative rates have been reported. The extent of urbanization also contributes to extreme regional precipitation through the urban heat island effect and aerosol concentration (Dixon and Mote, 2003;Mölders and Olson, 2004;Guo et al, 2006;Mohsen and Gough, 2012;Wang et al, 2015). One of the first attempts to derive nonstationary IDF through the Bayesian inference (BI) approach for extreme value analysis was by Cheng and AghaKouchak (2014), where the authors introduced a linear trend in the parameters of the selected distribution.…”
Section: Introductionmentioning
confidence: 99%
“…On a local scale, for sub-hourly and up to 6-hourly extreme precipitation, increases at or above the C-C rate have been found in the Netherlands (Lenderink and van Meijgaard, 2008;Lenderink et al, 2017), Switzerland (Ban et al, 2014), Germany (Berg et al, 2013), the UK (Blenkinsop et al, 2015), the Mediterranean (Drobinski et al, 2016), most of Australia Sharma, 2015, 2017;Schroeer and Kirchengast, 2017), North America (Shaw et al, 2011), and China (Miao et al, 2016), while in India (Ali and Mishra, 2017) and northern Australia (Hardwick Jones et al, 2010) negative rates have been reported. The extent of urbanization also contributes to extreme regional precipitation through the urban heat island effect and aerosol concentration (Dixon and Mote, 2003;Mölders and Olson, 2004;Guo et al, 2006;Mohsen and Gough, 2012;Wang et al, 2015). One of the first attempts to derive nonstationary IDF through the Bayesian inference (BI) approach for extreme value analysis was by Cheng and AghaKouchak (2014), where the authors introduced a linear trend in the parameters of the selected distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of climate change on precipitation extremes have been of concern to many researchers in recent decades (Bao et al, ; Hartmann et al, ; Held & Soden, ; Qin & Xie, ; Seager et al, ). Canada is now suffering tremendous amounts of damage due to more frequent and severe precipitation extremes (Held & Soden, ; Seager et al, ; Wang et al, ; Zhou, Huang, Wang, et al, ). Recently, regional climate models (RCMs) have been widely employed to analyze the potential impacts of climate change under the Representative Concentration Pathways (RCPs; Van Vuuren et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Jeong, Sushama, Diro, Khaliq, Beltrami, et al (2016) analyzed the projected changes in hot days, hot spells, and heat waves in a Canadian context by using 11 RCM simulations from the North American Regional Climate Change Assessment Program. Wang et al (2015) developed highresolution climate projections over Ontario, Canada, to assess plausible impacts of climate change through an ensemble modeling approach. Mladjic et al (2011) developed projections of extreme precipitation changes over Canada for the Special Report on Emissions Scenarios A2 by using the Canadian Regional Climate Model.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has already been manifested in a range of ways and poses serious threats to all aspects of our living environment (Rai and Gurung, 2005;Butt et al, 2012;Wang et al, 2013Wang et al, , 2014a, such as crop yield, food security, forest coverage, water quality and quantity, animal husbandry and aquaculture, and aquatic product breeding (Easterling and Apps, 2005;McMichael et al, 2006;Noyes et al, 2009;Nursey-Bray et al, 2012;Keenan, 2015;Wang et al, 2015c). Understanding the ongoing climatic changes is very important for human subsistence and sustainable development of the economy and society (Jordan et al, 2014;Jozsa et al, 2014;Shi et al, 2014;Wang et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%